Cytotoxic constituents of Cymbidium tracyanum L.Castle - Nonthalert Lertnitikul, Rutt Suttisri, Khin Lay Sein, Suree Jianmongkol, Cherdsak Boonyong, Witchuda Thanakijcharoenpath (Journal of Applied Pharmaceutical Science, 2024)
Three phenanthrene derivatives, cymbisamoquinone (1), calanquinone B (6), and 3,7-dihydroxy-2,4,6- trimethoxyphenanthrene (2), and two bibenzyls, Tristin (3) and gigantic (4), together with the lignan (+)-pinoresinol (5), were isolated from the whole plants of Cymbidium tracyanum L.Castle (Orchidaceae). Their structures were determined through spectroscopic analysis as well as a comparison of the spectral data with literature values. The phytochemical constituents of this plant have been reported for the first time. All isolated compounds were evaluated for in vitro cytotoxic activity against human colon (Caco-2) and breast (MCF-7) cancer cell lines, doxorubicin-resistant (MCF-7/DOX) and mitoxantrone-resistant (MCF-7/MX) MCF-7 sublines, together with normal human fibroblast (NIH/3T3) cell line. Among the isolated compounds, 1 exhibited the strongest and relatively selective activity on MCF-7/DOX cells. The results obtained from the molecular docking study suggested that the cytotoxicity of 1 on MCF-7/DOX cells was possibly due to the induction of apoptosis via suppression of the cell survival systems mediated by the mitogen-activated protein kinases and protein kinase B/glycogen synthase kinase-3β/nuclear factor erythroid 2-related factor 2 signalling pathways.
Keywords: Cymbidium tracyanum, cymbisamoquinone, phenanthrenequinones, phenanthrenes, bibenzyls, cytotoxic activity